Re-evaluating 'feminism' in the art practice of Amanda Heng from the 1990s to the present - Chang, Natalie Min (Nanyang Technological University, 2022)
This study is an urgent call to redress the conflicting definitions of ‘feminism’ in Singapore and its resulting effect in the study of the Singaporean artist Amanda Heng. It seeks to understand how certain labels – such as “feminist” – promote essentialist tendencies that ignore the diverse differences in the study of (women) artists in Singapore and Southeast Asia. Can women ever be perceived outside of their prescribed gender roles? Can a woman artist ever be defined as merely an artist? How has feminism/-s abetted or hindered specifically gender-centric discourses in Singapore and Southeast Asian contemporary art history? Taking these questions as a starting point, the study proposes a repositioning of feminist parameters that have restricted Heng’s practice while subtly addressing the intersectional concerns of women’s experience in the mainstream. Through an analysis of the artist’s work from the 1990s to the present, it will examine aspects of community and collaboration by bringing into focus the universal aspects of cultural and collective memory. Although performance art has become an important mainstay in Heng’s practice, this study will instead focus on her more project-based and collaborative work as a means of identifying how her practice has evolved over time. Such a focus allows for parallel contemplation of her early and more recent work by instigating dialogue between the two with each other. The study concludes by highlighting the language of feminism that Heng has adapted in creating a discourse of gender that benefits society as a whole. In so doing, it argues that Heng has used this language to call into question and break down the different hierarchies of gender, domestic labour, and the role of the artist within her practice.